An experimental study on the additional settlement of footings resting on granular soils by water table rise - Morgan B.A.; Shukla S.K.; Sivakugan N. (My University, 2025)
When the water table rises in a granular soil mass, a large additional settlement of footing resting on such a soil mass is commonly expected. Laboratory model tests show that when the water table rises to the footing level, there can be an additional 400 to 500% of the settlements compared to when the soil is dry. To understand the mechanics of the additional settlements of footings resting on the granular soil masses caused by water table rise, an investigation into the change in the Young's modulus of soil was therefore made using oedometer tests. A relation between the saturated and the dry Young's moduli of the granular soils is presented for use in the elastic analysis of footing settlements. The findings of the investigation were then used to predict the additional settlements of a model footing when subjected to a water table rise, using elastic analysis. The theoretical predictions of the additional settlements are lower than the actual additional settlements observed in the settlement tests conducted in the laboratory using model tests. The model tests show that the additional settlements are larger in loose sands than in dense sands.